DEKONSTRUKSI TAFSIR AYAT-AYAT KEKERASAN - Abdillah, Junaidi (Analisis: Jurnal Studi Keislaman, 2011)
In the radicalist circle, Islam is a source to legitimize their behavior, though it is counter productive with the Qur’an which not absolutely allow violence on behalf  of  God. This writing is a critic against its abuse of inter pretation. Thematic approach is applied to analyze verses which are usually used to justify violences. Surveying on the verses is a tool to analyze for the pur pose of finding true meaning of the text. The unproper inter pretation of  jiha>d (struggle) caused it trapped in violence and radicalism. Whereas the general context of  jiha>d does not relate with a war.